Draft Annual Plan 1987-88 Volume-I Government of Arunachal Pradesh - Planning Commission (Planning Commission, 1987)
The Union Territory of Arunachal Pradesh has a population of 6.32 lakhs spread over an area of 83,743 Sq.Kms. It ranks 13th in size amongst the 22 States and the 9 Union Territories in the country. the UT has 3257 villages and is predominantly tribal. According to the 1981 Census, the territory had a density of 7.5 persons per Sq.Km. Out of total population of 6.32 lakhs 53.5% were males and 46.5% were females. In numerical terms males numbered 3.49 lakhs and females 2.93 lakhs. the sex ratio of the territory was 862 females per thousand males.
Government of Arunachal Pradesh, Planning and Development Department